AWARENESS AND HEALTH SEEKING BEHAVIOUR OF PARENTS REGARDING THEIR CHILDREN’S ORAL HEALTH AND PROFESSIONAL DENTAL CARE - NOREEN , N; FATEMAH , H; YOUSFANI , J; MANSOOR , A; MANSOOR , E; ULLAH , H (Biological and Clinical Sciences Research Journal, 2024)
Parents’ awareness and health-seeking behaviour concerning their children’s oral health and professional dental care are vital components shaping pediatric dental wellness. The study’s primary objective is to find parents’ awareness and health-seeking behaviour regarding their children’s oral health and professional dental care. This cross-sectional study was conducted in Karachi. Data was collected from 320 parents who participated in this study. To capture a comprehensive understanding, participant recruitment involves a diverse selection of parents, ensuring representation across various demographics, including age, socioeconomic status, educational background, and geographical location. Data were collected from 320 participants. Participants belong to different age groups. Respondents with a high school education or less constituted 35%, while those with a bachelor’s degree represented 30% of the participants. The survey outlined varying degrees of parental awareness regarding specific oral health practices. While a high percentage of parents were aware of the importance of fluoride use for children (85%) and the ideal age for dental check-ups (60%), adherence to the American Academy of Pediatric Dentistry (AAPD) brushing recommendations and awareness of proper flossing techniques were notably lower, at 25% and 40%, respectively. It is concluded that early dental checkups play a crucial role in preventing conditions like dental caries. Founding good oral habits and hygiene during the formative years significantly contributes to lifelong oral health in children.